PERBEDAAN INTENSITAS NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III SEBELUM DAN SETELAH DIBERIKAN TERAPI GYM BALL - SARI, RATNA PUSPITA (JURNAL MEDIKA USADA, 2025)
Abstract Intoduction: Reducing pain is done with therapy using a gym ball. The aim of the research was to determine the difference in the intensity of lower back pain in third trimester pregnant women, before and after being given gym ball therapy at the independent practice of midwife Ni Made Mariyati, S.Tr.Keb. Methods: This type of research is a quasi experiment with a one group pretest posttest design. Quasi-experiment. Intervention with gym ball therapy. The sample size of 21 people was taken by purposive sampling. Data analysis with Wilcoxon. Result: The results of the study before the intervention were that the highest pain level was 3 (57.2%), the median was 3, the lowest pain score before the intervention was given was a median of 3 and a mean of 3, after being given the intervention a median of 1 and a mean of 1.2, p value 0.001. There was a change in pain scores before and after being given gym ball therapy, this was because it helped stimulate postural reflexes which helped reduce pain. Suggestion: Regular and continuous check-ups need to be carried out to control the health condition of teenage girls to prevent problems or disturbances in their health and nutritional status. Keywords: Pregnant Women, Back Pain, Gymnastics Ball